2007
DOI: 10.1111/j.1439-0507.2007.01403.x
|View full text |Cite
|
Sign up to set email alerts
|

A 7‐year survey of dermatophytoses in Crete, Greece

Abstract: Dermatophytoses are of worldwide distribution. Epidemiological studies concerning dermatophyte infections have been performed in many countries and differences in the incidence and the aetiological agents have been reported in different geographical locations. This study was undertaken to investigate the prevailing species of dermatophytes in the island of Crete, Greece, and their pattern of infection during a 7-year period (1997-2003). A total of 5544 samples obtained from 3751 patients with clinically suspec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
39
4
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 31 publications
10
39
4
2
Order By: Relevance
“…In Greece, T. rubrum is also predominant, as demonstrated in a study conducted in Crete between 1992 and 1996 in which T. rubrum was the most frequent dermatophyte (44.4 %) isolated, followed by M. canis (24 %), T. interdigitale (3.4 %) and T. verrucosum (1.8 %) [31]. A few years later (1997)(1998)(1999)(2000)(2001)(2002)(2003), the same authors reported the same dermatophyte distribution: T. rubrum (48 %), M. canis (17.9 %), T. interdigitale (14.2 %), E. floccosum (6 %) [32,33]. In Spain, while few studies are available, a 5-year retrospective survey performed in a dermatology clinic in Zaragoza during the period 1991-1995 showed a predominance of M. canis (44 %) associated with tinea corporis, followed by T. mentagrophytes and T. rubrum (18.6 %) [34].…”
Section: Trends In Epidemiology Evolution Of Dermatophytosis In Europmentioning
confidence: 50%
“…In Greece, T. rubrum is also predominant, as demonstrated in a study conducted in Crete between 1992 and 1996 in which T. rubrum was the most frequent dermatophyte (44.4 %) isolated, followed by M. canis (24 %), T. interdigitale (3.4 %) and T. verrucosum (1.8 %) [31]. A few years later (1997)(1998)(1999)(2000)(2001)(2002)(2003), the same authors reported the same dermatophyte distribution: T. rubrum (48 %), M. canis (17.9 %), T. interdigitale (14.2 %), E. floccosum (6 %) [32,33]. In Spain, while few studies are available, a 5-year retrospective survey performed in a dermatology clinic in Zaragoza during the period 1991-1995 showed a predominance of M. canis (44 %) associated with tinea corporis, followed by T. mentagrophytes and T. rubrum (18.6 %) [34].…”
Section: Trends In Epidemiology Evolution Of Dermatophytosis In Europmentioning
confidence: 50%
“…2 In the present study commonest causative agent is dermatophyte which is observed in most of the studies on onychomycoses conducted in India and outside the India. 4,7 Amongst the dermatophyte T. rubrum was most common isolate (42%) followed by T. mentagrophyte and E. flocossum. Jha et al find the same observation in study on superficial mycoses and T. mentagrophyte followed by T. rubrum and E. flocossum Scher et al found that rate of isolation of T. mentagrophytes and T. rubrum was very high which can be explained on the basis of its capacity to infect the hard keratin of the nail.…”
Section: Resultsmentioning
confidence: 99%
“…Dermatophytes are classified into three habitual species as Anthropophilic, Zoophilic, and Geophilic species in an environment [12] [32] [33]. Their habitat depends on the survival host as human, animals and soil [34] [35].…”
Section: Classification Based On Natural Habitatmentioning
confidence: 99%